Human and monkey infant attention to dynamic social and nonsocial stimuli - Maylott, Sarah E. (Dev Psychobiol, 2020)
The present study explored behavioral norms for infant social attention in typically developing human and nonhuman primate infants. We examined the normative development of attention to dynamic social and nonsocial stimuli longitudinally in macaques (Macaca mulatta) at 1, 3, and 5 months of age (N=75) and humans at 2, 4, 6, 8, and 13 months of age (N=69) using eye tracking. All infants viewed concurrently played silent videos—one social video and one nonsocial video. Both macaque and human infants were faster to look to the social than the nonsocial stimulus, and both species grew faster to orient to the social stimulus with age. Further, macaque infants’ social attention increased linearly from 1 to 5 months. In contrast, human infants displayed a non-linear pattern of social interest, with initially greater attention to the social stimulus, followed by a period of greater interest in the nonsocial stimulus, and then a rise in social interest from 6 to 13 months. Overall, human infants looked longer than macaque infants, suggesting humans have more sustained attention in the first year of life. These findings highlight potential species similarities and differences, and reflect a first step in establishing baseline patterns of early social attention development.